PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL ECOLINK DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS - Husain, Putra Ismail; PanaI, Abdul Haris; Arif, Rifda Mardian; Arifin, Irvin Novita; Arifin, Vicka Muniati (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2025)
This research aimed to develop a digital learning medium called Ecolink that meets the criteria of feasibility, practicality, and effectiveness in IPAS (Science, Social Studies, and Arts) learning to improve student learning outcomes on the topic of Environmental Changes and Waste Management at SDN 98 Kota Utara. This study employed the Research and Development (R&D) method, utilizing the ADDIE development model, which includes the stages of analyze, design, development, implement, and evaluate. Through validation by experts and users, the Ecolink digital learning medium obtained a recapitulation of average feasibility scores with a percentage of 94.6%, categorizing it as highly feasible for use by teachers and students in elementary schools. For the practicality test of the Ecolink digital learning medium, researchers used teacher observation sheets. The practicality percentage for using the Ecolink digital learning medium in learning reached 95%, which falls into the highly practical category. Regarding the effectiveness of the Ecolink digital learning medium during its implementation in Class V of SDN 98 Kota Utara, researchers administered a learning outcome test to measure its effectiveness. The total pretest score was 37.72%, while the total posttest score reached 85.90%. The N-Gain calculation showed a value of 0.77, which is categorized as "High." Based on these recapitulation results, it can be concluded that the Ecolink digital learning medium can improve student learning outcomes and is highly effective for use in elementary schools. In conclusion, the developed Ecolink digital learning medium proved to be highly feasible, practical, and effective for use in the learning process. ABSTRAKTujuan pada penelitian ini adalah mengembangkan media pembelajaran pembelajaran digital Ecolink yang memenuhi kriteria kelayakan, kepraktisan, dan efektivitas dalam pembelajaran IPAS guna meningkatkan hasil belajar siswa pada materi Perubahan Linkungan dan Pengelolaan Sampah di SDN 98 Kota Utara. Penelitian ini menggunakan metode (Research and Development) dengan menggunakan model penelitian pengembangan ADDIE, yang mencakup tahapan analyze, design, development, Implement, dan Evaluate. Melalui validasi oleh para ahli dan pengguna, media pembelajaran digital Ecolink memperoleh hasil rekapitulasi nilai rata-rata kelayakan dengan presentase 94,6% dan dinyatakan sangat layak digunakan oleh guru dan siswa di sekolah dasar. Dalam uji kepraktisan media pembelajaran digital Ecolink, peneliti menggunakan instrument lembar observasi guru dengan presentase kepraktisan penggunaan media pembelajaran digital Ecolink dalam pembelajaran mencapai 95%, yang termasuk kedalam kategori sangat praktis. Dalam keefektifan media pembelajaran digital Ecolink pada saat penerapan media di kelas V SDN 98 Kota Utara, peneliti membagikan tes hasil belajar untuk mengukur keefektifan media.  Total nilai pretest adalah 37.72%, sedangkan total nilai posttest mencapai 85.90%. Perhitungan N-Gain menunjukan nilai sebesar 0,77 yang termasuk dalam ketegori “Tinggi”. Dengan hasil rekapitulasi ini maka dapat dinyatakan bahwa media pembelajaran digital Ecolink dapat meningkatkan hasil belajar siswa dan sangat efektif digunakan di sekolah dasar. Kesimpulan pada penelitian pengembangan media pembelajaran digital Ecolink yang dikembangkan terbukti sangat layak, praktis, dan efektif digunakan dalam proses pembelajaran